Peran Strategi Rebranding Dan Brand Image Terhadap Keunggulan Bersaing Pada CV. Roughrebel Abadi Sukabumi - Gery J Pangestu; Erry Sunarya; Faizal Mulia Z (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2022)
This study aims to determine the effect of Rebranding and Brand Image on competitive advantage in CV. Roughrebel Abadi Sukabumi. The method used in this research is descriptive method and associative method with a quantitative approach. The sampling technique used is accidental sampling, the sample to be taken by the author is 372 students of Muhammadiyah University of Sukabumi who know Rough and Rebel Sukabumi. The data analysis technique used is multiple linear regression analysis which includes the coefficient of determination, multiple correlation coefficient, simultaneous test (F test) and partial test (T test). The results of the study using the F test the probability value of sig. 0.00 < 0.05 which means that together Rebranding and Brand Image have a significant effect on competitive advantage in CV. Roughrebel Abadi Sukabumi. While the t test shows that Rebranding has a significant effect on competitive advantage and Brand Image has a significant effect on competitive advantage. Keywords: Rebranding, Brand Image, Competitive Advantage